Scandinavian-Saami religious connections in the history of research - Rydving, Håkan (Scripta Instituti Donneriani Aboensis, 1990)
The religions of Scandinavians and Saamis have, for decades of scholarship, functioned as sources of analogies to explain elements in one another. For the study of Saami religion answers to questions about origins were sought in Scandinavian religion, while Saami religion has been seen by students of Scandinavian religion, as a preserver and a faithful witness of Scandinavian concepts and rites that had vanished in the times reflected in the literary sources. This view has now changed. In recent decades the tendency has been to use the loan- explanations more and more sparsely. Elements in Saami religion that were seen earlier as Scandinavian loans are now explained in a Finno-Ugric context, whereas the few elements in Scandinavian religion that were thought of as loans from the Saamis are more often looked upon as inherited from a common origin, a North Eurasian cultural stratum. The search for analogies has, in any case, preoccupied the historian of religions in this field, too. The purpose here is to provide a short and selective résumé of some aspects of a theme in the history of scholarship, a theme where "resemblances" have been found, compared, used as analogies, and — called into question: the comparative study of the religions of the Scandinavians and Saamis.